ANALISIS PENGARUH KOMUNIKASI ORGANISASI DAN KOMITMEN KEORGANISASIAN TERHADAP KEPUASAN KERJA KARYAWAN PT. BTPN TBK KCP PASAR BARU MERANGIN - Mustika . (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
This research was conducted at PT Bank BTPN.Tbk KCP Merangin wich has total employee 23 people. The research method used was survey that used questionnaire to collect the data. Data analysis used Regression Analysis, that intended to examine simulatan and partial relationship. Research result shows that the ability of Regression to explain dependent variable is 25,7 percentage and Pvalue (0,05) shows that it is not significant relationship. Hence, the research should explore more variable that could explaind emplyee’s job satisfaction on PT. BTPN, Tbk. Keywords: communication, Organizational Commitment and job satisfaction